1995
DOI: 10.1073/pnas.92.13.5930
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally related responses of maize catalase genes to salicylic acid.

Abstract: The response of the maize catalase genes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(88 citation statements)
references
References 29 publications
5
82
0
1
Order By: Relevance
“…It was shown that the pre-soaking of pea seeds in SA had a beneficial effect on growth and photosynthesis, and led to a decrease in the oxidative injuries caused by heavy metal stress (Hayat et al 2010). It was also noted that a dramatic inhibition of the germination process was reported above a concentration of 1 mmol in maize (Guan and Scandalios 1995) and Arabidopsis (Rajjou et al 2006) plants. However, a complete understanding of the effect of exogenous SA applied as a foliar spray is still lacking.…”
Section: Discussionmentioning
confidence: 91%
“…It was shown that the pre-soaking of pea seeds in SA had a beneficial effect on growth and photosynthesis, and led to a decrease in the oxidative injuries caused by heavy metal stress (Hayat et al 2010). It was also noted that a dramatic inhibition of the germination process was reported above a concentration of 1 mmol in maize (Guan and Scandalios 1995) and Arabidopsis (Rajjou et al 2006) plants. However, a complete understanding of the effect of exogenous SA applied as a foliar spray is still lacking.…”
Section: Discussionmentioning
confidence: 91%
“…CATs encompass a large family of proteins, which can be found in almost every oxygen-requiring microorganism, animal and plant. [11] There are three members identified in Arabidopsis thaliana [28], Nicotiana tabacum [29] and Zea mays [30]; and two in Hordeum vulgare [31] and Solanum lycopersicum. [32] In the catalase gene family, different members encode distinct catalase enzymes.…”
Section: Numbers Of Variation Sites Type Of Variation Sitesmentioning
confidence: 99%
“…Thus, their results may indicate the interaction of salt stress and light stress. It should also be noted that the plant defense associated hormone salicylic acid (SA) can regulate H 2 O 2 levels and may interact with ABA (Guan and Scandalios 1995;Rai et al 1986). Thus, altered SA levels or signaling could also contribute to the phenotypes of shmt1-1 as well as ggt1-1 and ndpk2.…”
Section: Increased Ros Levels Stimulate Aba-induced Pro Accumulationmentioning
confidence: 99%